The Influence of Human Resource Management Strategies on Employee Loyalty at Emersia Hotel & Resort Bandar Lampung - Putra, Dodi; Rinova, Dora; Santoso, Niki; Handayani, Agustuti (Journal of Advances in Accounting, Economics, and Management, 2025)
This study aims to determine the effect of human resource management (HRM) strategies on employee loyalty at Emersia Hotel & Resort Bandar Lampung. In today's competitive hospitality industry, employee loyalty is crucial to ensure consistent service quality, customer satisfaction, and organizational sustainability. The research focuses on six indicators of HRM strategy: recruitment and selection, training and development, compensation and benefits, performance appraisal, career development, and organizational culture and communication. The loyalty variable is assessed through affective commitment, normative commitment, willingness to exert extra effort, and intention to stay. This research employs a quantitative approach with data collected through questionnaires distributed to 45 employees selected using random sampling. The validity and reliability of the instruments were tested using SPSS. The results of the Pearson correlation analysis indicate a significant positive relationship between HRM strategies and employee loyalty. The coefficient of determination (R²) shows that HRM strategies explain 65.6% of the variation in employee loyalty. Furthermore, hypothesis testing confirms that HRM strategies significantly influence employee loyalty.The findings suggest that effective implementation of HRM strategies can foster a more committed and loyal workforce. This implies that organizations in the hospitality sector should invest in strategic HR practices to enhance employee satisfaction and retention.